Structure of native glycolipoprotein filaments in honeybee royal jelly - Simone Mattei (Nature Communications, 2020)
Female honeybee larvae develop into queens when they are fed exclusively with royal jelly (RJ) and major royal jelly protein 1 (MRJP1) is the main protein component of RJ. Here, the authors present the 3.5 Å cryo-EM structure of native RJ filament, where MRJP1 forms the outer shell surrounding apisimin tetramers with bound lipids at the core of the filament.